THE THEORY OF IMPROVING THE METHODOLOGY OF TEACHING TERMINOLOGICAL LEXICON TO STUDENTS IN THE DIRECTION OF ELECTRICAL ENERGY (International Conference on Economics, Finance, Banking and Management, 2025)
The article explores the theory of enhancing the methodology of teaching terminological lexicon to students specializing in electrical energy. It discusses the need for systematic development of terminological competence, effective teaching approaches, and innovative strategies to enhance learning outcomes. The research highlights practical methods, including integrative approaches and technological tools, to improve the acquisition and usage of specialized terminology.